2012
DOI: 10.1177/0194599812442059
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vestibular Caloric Tests in Cochlear Implantation

Abstract: Although cochlear implantation may result in dizziness, it is almost always short-lived and mild, even when the ear with the stronger caloric response is implanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Ideally, until more is known about how cochlear implantation affects specific vestibular end organs, preoperative testing would identify the weaker ear using a broad panel of tests examining both canal function (such as with head impulse testing or caloric testing) and otolith function (provided by cVEMP and oVEMP tests, respectively). This recommendation is substantially different than may be drawn from another study, which reported that implantation on the stronger side (as measured by calorics) did not increase the chance of subjective dizziness postoperatively and could be used to justify not measuring balance function preoperatively [Parmar et al, 2012]. The conclusions of that article seem too optimistic given the lack of correspondence between symptoms of imbalance and actual balance testing, such as used here, which can quantify fall risk.…”
Section: Mitigation Of Imbalancementioning
confidence: 72%
“…Ideally, until more is known about how cochlear implantation affects specific vestibular end organs, preoperative testing would identify the weaker ear using a broad panel of tests examining both canal function (such as with head impulse testing or caloric testing) and otolith function (provided by cVEMP and oVEMP tests, respectively). This recommendation is substantially different than may be drawn from another study, which reported that implantation on the stronger side (as measured by calorics) did not increase the chance of subjective dizziness postoperatively and could be used to justify not measuring balance function preoperatively [Parmar et al, 2012]. The conclusions of that article seem too optimistic given the lack of correspondence between symptoms of imbalance and actual balance testing, such as used here, which can quantify fall risk.…”
Section: Mitigation Of Imbalancementioning
confidence: 72%
“…As they used bithermal caloric testing, this means that the function of the utricle, saccule, and other semicircular canals was not tested. In addition, caloric testing may not entirely reflect the physiological function of the lateral canal as it mimics only low frequency stimulation [25].…”
Section: Resultsmentioning
confidence: 99%
“…Parmer et al investigated the relationship between post-operative dizziness and cochlear implantation in the ear with the weaker caloric response. 3 These authors found no differences in post-operative dizziness in patients implanted on the side with the weaker caloric response by pre-operative ENG testing. However, they found impaired visual fixation suppression, an indicator of central involvement, to be a major risk factor for post-operative dizziness.…”
Section: Introductionmentioning
confidence: 90%
“…In the setting of asymmetric caloric responses, it has been recommended that the ear with the poorer caloric response should be preferentially selected for cochlear implant so as to preserve the ear with the better vestibular function and minimise postoperative vestibular symptoms. 3 The utility of pre-operative ENG in predicting postoperative vestibular symptoms is unclear. In a retrospective review, Fina et al found no significant difference in pre-operative caloric test results among cochlear implant recipients with and without postoperative dizziness.…”
Section: Introductionmentioning
confidence: 99%